2017
DOI: 10.1002/ejsp.2268
|View full text |Cite
|
Sign up to set email alerts
|

An application of the prototype willingness model to drivers' speeding behaviour

Abstract: We tested the prototype willingness model (PWM). The participants (N=198) completed online questionnaire measures of PWM constructs (time 1) and subsequent speeding behaviour (time 2). Path analyses showed that the PWM accounted for 89% of the variance in subsequent (self-reported) speeding behaviour. This significantly exceeded the variance accounted for by the theory of planned behaviour. In line with the PWM, both behavioural intention and behavioural willingness had direct effects on behaviour. Behavioural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 62 publications
(112 reference statements)
6
25
0
Order By: Relevance
“…Interestingly, our findings showed that RLR intention and willingness were crucial predictors of RLR behavior, and the total effect of willingness on RLR behavior was prominently stronger than that of intention. Elliott et al [47] and Demir et al [21] ey also revealed that behavioral willingness contributed more substantially to violating behavior than behavioral intention. us, we concluded that e-bikers might decide on whether to violate a red light through the social reactive pathway rather than the reasoned pathway.…”
Section: Predictive Utility Of Pwm and Tpb-pwmmentioning
confidence: 96%
See 1 more Smart Citation
“…Interestingly, our findings showed that RLR intention and willingness were crucial predictors of RLR behavior, and the total effect of willingness on RLR behavior was prominently stronger than that of intention. Elliott et al [47] and Demir et al [21] ey also revealed that behavioral willingness contributed more substantially to violating behavior than behavioral intention. us, we concluded that e-bikers might decide on whether to violate a red light through the social reactive pathway rather than the reasoned pathway.…”
Section: Predictive Utility Of Pwm and Tpb-pwmmentioning
confidence: 96%
“…e PWM framework, which focuses on both social reactive decision-making and reasoned one, might contribute to a better understanding of RLR behavior than TPB framework, which is concentrated on reasoned decision-making only. e PWM framework has been successfully applied in examinations of drivers' and pedestrians' violations, such as drink-driving [46], high-speeding [47,48], texting while driving [48], and pedestrians' violations [21]. As far as we are concerned, no previous research studies have employed the PWM framework in the study on e-bikers' violations.…”
Section: Pwm Frameworkmentioning
confidence: 99%
“…In an attempt to identify predictors of speeding, many studies have focused on the relationship between attitudes (positive/negative evaluations) and behaviour (e.g., Conner, Lawton, Parker, Chorlton, Manstead & Stradling, 2007;Elliott, Thomson, Robertson, Stephenson & Wicks, 2013;Elliott, McCartan, Brewster, Coyle, Emerson & Gibson, 2016;Lheureux, Auzoult, Charlois, Hardy-Massard, & Minary, 2015). In these and studies of other driving behaviours (e.g., Elliott, 2012) it has been found that attitudes are statistically reliable predictors of behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the relative importance of the predictors of behavioural willingness, like the reasoned path, attitudes seem to be the strongest predictor of behavioural willingness, followed by norms, and prototype favourability (Gerrard et al, 2002;. Furthermore, tests of the PWM suggest that willingness may be a stronger predictor of behaviour than behavioural intention, depending on age and experience with the behaviour (e.g., Elliott, McCartan, Brewster, Coyle, Emerson, & Gibson, 2017;Gibbons et al, 2009), though both concurrently predict later behaviour.…”
Section: Figure 2 the Prototype Willingness Modelmentioning
confidence: 93%
“…The prototype willingness model of behaviour has been used to examine a wide range of health behaviours including risky sexual behaviours and pregnancy , smoking (Gerrard et al, 2005), alcohol use (Davies, Paltoglou, & Foxcroft, 2017;Todd & Mullan, 2011), eating behaviours (Dohnke, Steinhilber, & Fuchs, 2015), physical activity (Frater, Kuijer, & Kingham, 2017), speeding (Elliott et al, 2017), and drinking and driving (Rivis, Abraham, & Snook, 2011). Across all these studies the three antecedents (norms, attitudes, prototype images) have been found to significantly predict intent and willingness to behave, among adolescents.…”
Section: Applicability Of the Prototype Willingness Modelmentioning
confidence: 99%